PENGARUH FAKTOR SOSIAL EKONOMI TERHADAP TINGKAT KESEJAHTERAAN DAN PARTISIPASI KELUARGA NASABAH : STUDI KASUS BANK SAMPAH LEMBAGA PEMBERDAYAAN MASYARAKAT KELURAHAN DAUH PURI, DENPASAR - Primajana Dewa Jati; Widanta Anak Agung Bagus Putu (PIRAMIDA, 2019)
Indonesia is the fourth most populous country with a population of 258 million peoples and will continue to grow over time. Increasing population will certainly increase the amount of consumption as well as the potential increase in the volume of waste produced by humans every day. Good waste management will have a good impact on the environment. To realize this the existence of Waste Bank is certainly very needed. In addition to providing a dampat on the surrounding environment, the Bank Trash can also create a creative industry that impact on the socio-economic customers. This research was conducted in Kelurahan Dauh Puri, Denpasar. Population in this research is citizen registered as customer of Trash Bank with sample using slovin formula amounted to 136 peoples. The method of determining the sample using proporsionate stratified random sampling. Data analysis technique used is path analysis and test of sobel to analyze indirect influence through intervening variable. The result of hypothesis testing shows that education level and employment status have positive and significant influence, while age has negative and significant effect to the welfare of customer of Waste Bank of Community Empowerment Institute of Dauh Puri. The level of education and employment status have a positive and significant influence, while the age, and the welfare have a negative and significant impact on the level of customer participation of the Bank Dump Institute of Community Empowerment Dauh Puri. Work participation variable is the variable of indirect effect of mediation and significant level of work, employment status and age to the welfare of customers of Waste Bank Community Empowerment Institute Dauh Puri.